Acute changes in plasma glucose increases left ventricular systolic function in insulin‐treated patients with type 2 diabetes and controls. Issue 6 (22nd March 2022) - Andersen, Andreas; Jørgensen, Peter G.; Bagger, Jonatan I.; Baldassarre, Maria P. A.; Christensen, Mikkel B.; Pedersen‐Bjergaard, Ulrik; Lindhardt, Tommi B.; Gislason, Gunnar; Knop, Filip K.; Vilsbøll, Tina
Abstract: Aims: We aimed to evaluate the effect of acute hyperglycaemia and hypoglycaemia on cardiac function in patients with type 2 diabetes (T2D) and a control group. Materials and methods: In a nonrandomized interventional study, insulin‐treated patients with T2D (N = 21, mean ± SD age 62.8 ± 6.5 years, body mass index [BMI] 29.0 ± 4.2 kg/m 2, glycated haemoglobin [HbA1c] 51.0 ± 5.4 mmol/mol [6.8 ± 0.5%]) and matched controls (N = 21, mean ± SD age 62.2 ± 8.3 years, BMI 29.2 ± 3.5 kg/m 2, HbA1c 34.3 ± 3.3 mmol/L [5.3 ± 0.3%]) underwent one experimental day with plasma glucose (PG) clamped at three different 30‐minute steady‐state levels: (1) fasting plasma glucose (FPG); (2) hyperglycaemia (FPG + 10 mmol/L); and (3) hyperinsulinaemic hypoglycaemia (PG <3.0 mmol/L). Cardiac function was evaluated during each steady state by echocardiography. Results: Acute hyperglycaemia increased left ventricular (LV) ejection fraction from baseline in patients with T2D (mean [95% confidence interval] 4.5 percentage points [1.1; 7.9]) but not in controls (2.0 percentage points [−1.4; 5.4]). Mitral annular peak systolic velocity (s′) increased during hyperglycaemia in both patients and controls (0.4 m/s [0.2;0.6] and 0.6 m/s [0.4; 0.8], respectively), whereas global longitudinal strain rate only increased in the controls (−0.05 s −1 [−0.12; 0.02] and −0.11 s −1 [−0.18; −0.03], respectively). All measures of LV systolic function increased markedly during hypoglycaemia ( P  <0.01 for all). No interaction between group and PG level on cardiac function was observed. Conclusions: Acute hyperglycaemia and hypoglycaemia increase LV systolic function, with no difference between patients with T2D and controls. Standardization of PG may improve reproducibility when evaluating LV systolic function in patients with T2D.